115k views
5 votes
Solve the system by elimination 2x - 2y = 6 and 3x + 2y = 9

User Zeratas
by
5.2k points

2 Answers

2 votes

Answer:

(3,0)

Explanation:

2x - 2y = 6

3x + 2y = 9

We are using elimination. Add the two equations together to eliminate y

2x - 2y = 6

3x + 2y = 9

----------------------

5x +0 = 15

5x=15

Divide each term by 5

5x/5 = 15/5

x = 3

Now we need to find y

3x+2y =9

3(3) +2y = 9

9+2y =9

Subtract 9 from each side

9-9 +2y =9-9

2y =0

Divide each side by 2

2y/2=0/2

y=0

User Nourdine
by
5.7k points
2 votes

Answer:

X=3,y=0

Explanation:

This is elimination method which is under the topic simultaneous equation

2x-2y=6...(1)

3x+2y=9...(2)

Add (1) and (2)

It gives

5x=15

Make x the subject of formula by dividing both sides by 5

x=3

Let's substitute the value of x in (2)

3(3)+2y=9

9+2y=9

Collect like terms

2y=9-9

2y=0

y=0

Therefore x is 3,y is 0

User Yenshirak
by
5.7k points